Decisiones de carácter sancionatorio proferidas por la Superintendencia de Industria y Comercio para la protección de los datos personales en Colombia entre los Años 2014 a 2019 (2020)
In this work, the documentary analysis of the sanctioning decisions that have been issued by the Superintendency of Industry and Commerce during the years 2014 to 2019, developed in light of Law 1581 of 2012 and its Regulatory Decree 1377 of 2013, is carried out. Regarding the protection of personal data in Colombia. We begin with the identification of the project, the formulation of the problem, the general and specific objective to be developed. The frame of reference is exposed through writings and articles by different authors who analyzed the evolution of the law of Habeas. After understanding the development in the Colombian context, the legal and regulatory framework regarding personal data is presented, identifying a regulatory framework, the norm and the issues that regulate it. The approach to law is supported by the theoretical vision of the French sociologist Pierre Bourdieu, who conceives of law from the perspective of legal fields. The legal framework addresses the interpretation of the 15th Constitutional fundamental right that all people have to their personal, family and good name. Finally, the work on the development of the specific objectives is supported: first, the structure of Law 1581 of 2012. Second, the presentation of the information from the analysis of the documentary review of 94 sanctioning decisions issued by the SIC during the years 2014 to 2019, identifying the facts and omissions of those in charge of the processing of personal data within the framework of General Law 1581 of 2012.